'Socialism will never be the same again'. Re-imagining British left-wing ideas for the 'New Times'. Issue 2 (3rd April 2017) - Campsie, Alexandre
Abstract: This article examines left-wing ideas about social change in the 1980s. It focuses on the 'New Times' debates, a series of discussions held in the Communist Party of Great Britain theoretical journal Marxism Today . The journal's key contributors contended that the profoundly transformed nature of 1980s Britain necessitated the adoption of revised political strategies. I historicise these claims by situating them within a longer tradition of British New Left analysis, and an engagement with post-1968 'new social movements'. I illustrate how Marxism Today 's vision of modernity was highly stylised. The journal's iconoclastic proclamations about apprehend the most strikingly modern forms. The 1980s were thus not entirely foreclosed by the parameters imposed by socio-economic transformations—a whole range of alternative ideas were on offer in this period. That this vibrant moment would give way to more reductive political solutions in the 1990s and beyond was not inevitable.